'Transfersome-embedded-gel' for dual-mechanistic delivery of anti-psoriatic drugs to dermal lymphocytes. (18th August 2022) - Todke, Pooja; Polaka, Suryanarayana; Raval, Nidhi; Gondaliya, Piyush; Tambe, Vishakha; Maheshwari, Rahul; Kalia, Kiran; Tekade, Rakesh Kumar
Abstract: Aim: Develop a platform for co-delivering clobetasol propionate (CP) and cyclosporine (CyA) to the epidermis and dermis to treat psoriasis. Methods: The transfersomes were prepared by thin-film hydration method. Transfersomes were characterised by dynamic light scattering and transmission electron microscope (TEM). Then, the gel stability, viscosity, pH, and spreadability were measured. Cytotoxicity of the CyA-loaded transfersome embedded in CP-dispersed gel (TEG-CyA-CP) was assessed on both human keratinocyte cell line (HaCaT) and Jurkat cells. In vitro cellular uptake and ex vivo dermal distribution was measured. The expression of inflammatory markers was assessed by reverse-transcription PCR (RT-PCR). Results: Nanoscale (<150 nm) transferosomes with high CyA encapsulation efficiency (>86%) were made. TEG-CyA-CP demonstrated higher viscosity (4808.8 ± 12.01 mPas), which may help control dual drug release. Ex vivo results showed TEG-CyA-CP ability to deliver CyA in the dermis and CP in the epidermis. RT-PCR studies showed the optimised formulation helps reduce the tumour necrosis factor (TNF-α) and interleukin-1 (IL-1) levels to relieve psoriasis symptoms. Conclusion: The developed TEG-CyA-CP represents a promising fit-to-purpose delivery platform for the dual-site co-delivery of CyA and CP in treating psoriasis.